Missouri Mathematics Project (MMP), Pemahaman Konsep Matematika, dan Kepercayaan Diri Siswa - Ni Pande Kadek Ayu Pratiwi; I Wayan Puja Astawa; Gusti Ayu Mahayukti (Jurnal Elemen, 2019)
This study aims to examine the effect of MMP learning models on understanding mathematical concepts and student confidence. The population of this study was students of class XI MIPA SMA Negeri 1 Semarapura academic year 2018/2019. The research instrument used was a test of understanding mathematical concepts and self-confidence questionnaires. This study is a quasi-experimental design with post-test only control group design. Data were analyzed using one-way multivariate variance analysis. The results showed that there were significant differences in the understanding of mathematical concepts and simultaneous self-confidence of students who followed the conventional MMP learning model. Furthermore, there were significant differences in understanding mathematical concepts and self-confidence of students who followed the conventional MMP learning model. From indicators of understanding concepts, classes with MMP and conventional learning models excel at indicators expressing concepts in their own words and weak on indicators identifying examples and not examples of concepts. Based on the aspect of self-confidence, the class with the MMP learning model is superior in the aspect of being responsible and weak in the optimistic aspects. Whereas, classes with conventional learning models excel in rational and realistic aspects, and are weak in aspects of self-ability confidence.